O universo das gentes do mar e a identidade negra nos discursos e práticas políticas de Carlos Santos : (1959-1974) - Gomes, Arilson dos Santos (2014)
The central focus of this thesis was to discuss Carlos da Silva Santos speeches (1904- 1989) in the gallery of the Assembly of Rio Grande do Sul, between the years 1959 and 1974, in that period the parlamantary remained as state representative Carlos da Silva Santos was important mediator in the process of construction of the current Brazilian public policies around fishing and black identity, which was once a participant in his political life, through his interventions plenary on these demands. His positions on the issues of workers of artisanal fishing and the black community are constituents of the identity of subject himself Carlos Santos, afro-brasilian born in of city seaside Rio Grande. Therefore, his positions were influenced by social forces that surrounded him. Through discourse analysis, interpret possibility of his actions and his presented projects may be related to the institucionalization of social, cultural demands, an, especially, the needs of policy development, political and social of these groups. Our theoretical perspective points to the renewed political history in turn, and the methodological choice of delimiting the documentary corpus was processed since the selection of this interventions, pointing out the two themed fields: the field of fishing activity and the one of the black identity. On assert that his interventions created conditions to the state and in Brazil. So, in this thesis, it was historically represented the universe of the social movements of the seapeople and the identity nuances of the black community in Carlos Santos political practices, taking aim to contribute for the historical knowledge of his protagonism in the mediation and in the preposition of laws on fishing benefit, of seapeople and the black community